2012
DOI: 10.1002/art.34604
|View full text |Cite
|
Sign up to set email alerts
|

The limited role of interferon‐γ in systemic juvenile idiopathic arthritis cannot be explained by cellular hyporesponsiveness

Abstract: Objective Systemic juvenile idiopathic arthritis (JIA) is an autoinflammatory syndrome in which the myelomonocytic lineage appears to play a pivotal role. Inflammatory macrophages are driven by interferon‐γ (IFNγ), but studies have failed to demonstrate an IFN‐ induced gene signature in active systemic JIA. This study sought to characterize the status of an IFN‐induced signature within affected tissue and to gauge the integrity of IFN signaling pathways within peripheral monocytes from patients with systemic J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
42
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 47 publications
6
42
0
Order By: Relevance
“…Our findings are similar to a study by Sikora et al [45], who showed that fresh, positively (CD14+) isolated, sJIA CD14+ monocytes from 4 active and 3 inactive sJIA patients did not exhibit hyporesponsiveness to IFNγ, as assessed by levels of pSTAT1. All the inactive sJIA patients were on IL-1 blockade and showed a higher fold increase in IFNγ-induced pSTAT1 than active patients or controls [45]. Interestingly, defective phosphorylation in response to IL-18 in sJIA NK cells was also restored following successful treatment with an IL-1 inihibitor [46].…”
Section: Discussionsupporting
confidence: 92%
“…Our findings are similar to a study by Sikora et al [45], who showed that fresh, positively (CD14+) isolated, sJIA CD14+ monocytes from 4 active and 3 inactive sJIA patients did not exhibit hyporesponsiveness to IFNγ, as assessed by levels of pSTAT1. All the inactive sJIA patients were on IL-1 blockade and showed a higher fold increase in IFNγ-induced pSTAT1 than active patients or controls [45]. Interestingly, defective phosphorylation in response to IL-18 in sJIA NK cells was also restored following successful treatment with an IL-1 inihibitor [46].…”
Section: Discussionsupporting
confidence: 92%
“…However, other studies of unstimulated autoimmune patient PBMCs compared with controls have also not detected baseline differences in phosphorylation of signaling molecules, including p-STAT1 and p-STAT2 in Addison's disease (30), p-ZAP70 in type 1 diabetes (31), and p-STAT1 in systemic JIA (32,33). The lack of differences in basal phosphorylation may be due to sample processing.…”
Section: Discussionmentioning
confidence: 83%
“…Consistently, patients with both active and inactive sJIA do not exhibit increased serum or synovial fluid IFNγ levels 27. Supporting the limited role of IFNγ in the arthritis of sJIA, and differently from what found in oligoarticular or polyarticular JIA, CXCL9 and CXCL10 are almost undetectable in the synovial tissues of patients with sJIA 28. Additionally, stimulation of IFNγ knockout mice with Freund's complete adjuvant produces a systemic inflammatory syndrome that includes features of sJIA 29…”
Section: Discussionmentioning
confidence: 83%